Tools and approaches for scaling out climate smart agriculture innovations in AICCRA Kenya - Nduah, Alex; Karanja, Regina; Ogutu, Liz; Nzuki, Esther (2024)
This report outlines the strategies employed for scaling CSA innovations in Kenya, leveraging value chain models, ICTs, policy engagements, and localized farmers and stakeholders training. By integrating these different approaches, the project has empowered over 5,000 farmers across diverse counties, focusing on arid and semi-arid lands. Collaborative partnerships, participatory piloting of CSA innovations, and capacity-building have fostered the widespread adoption of sustainable agricultural techniques, contributing to climate change resilience and food security among the AICCRA target beneficiaries, small-scale farmers in arid and semi-arid lands.